Mortgage market and extreme events : Case study of Ukraine. - Potiy, Kyrylo; de Batz de Trenquelléon, Laure Sabine Marie; Zezula, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis examines the Ukrainian mortgage market during COVID-19 pandemic and current full-scale Russian-Ukrainian war, uncovering insights into mortgage defaults during crises. By reviewing existing literature and conducting econometric analysis, the work highlights the complex relationship between economic factors and mortgage behavior. Key findings include clear link between rising primary housing prices and fewer loan defaults; challenges in following the traditional pattern that unemployment directly leads to more mortgage defaults; and other outcomes which are supported by the mortgage default theory. The research suggests the need for flexible policies and refined lending practices to mitigate risks. Despite data limitations, this thesis emphasizes the importance of continued research to promote financial stability in turbulent times.
Vedoucí práce: Laure Sabine Marie de Batz de Trenquelléon
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses